Long-term cognitive impairment following single mild traumatic brain injury with loss of consciousness: Findings from the Canadian Longitudinal Study on Aging. Issue 4 (20th April 2020) - Bedard, Marc; Steffener, Jason; Taler, Vanessa
ABSTRACT: Objective : We examined the extent to which loss of consciousness (LOC) following mild traumatic brain injury (mTBI) may be associated with impairments in executive functions and declarative memory more than a year after brain injury. Method : Analyses were run on 548 participants who had self-reported LOC of <1 min, 441 with LOC of 1–20 min, and 13, 609 no brain injury comparison participants, taken from the Canadian Longitudinal Study on Aging (CLSA), a nationwide study on health and aging. Results : Those that had mTBI with LOC of 1–20 min were more likely than no head injury comparisons to be impaired on measures of executive functioning and declarative memory. Impairments were evident when examining for single- and two-test impairment rates on measures of executive functioning and declarative memory. Conclusions : A subset of people that had reported a single mTBI with LOC more than 12 months ago may experience impairments in executive functioning and declarative memory, particularly those who spent more time unconscious.